Surgical Management of Chronic Rhinosinusitis in Cystic Fibrosis - Zheng, Zhong (Med Sci (Basel), 2019)
Cystic fibrosis patients frequently develop chronic rhinosinusitis as a result of their propensity to form inspissated mucus and impairment of mucociliary clearance. They exhibit variable symptom burden even in the setting of positive radiographic and endoscopic findings. Current evidence suggests a positive effect of managing sinonasal disease on pulmonary health. Topical antimicrobial and mucolytic therapies are frequently required to manage the disease with surgery reserved for refractory cases. Endoscopic sinus surgery has been demonstrated to be safe and efficacious in controlling symptoms of chronic rhinosinusitis in patients with comorbid cystic fibrosis. However, the impact of surgery on pulmonary health remains an active area of investigation. In addition, a growing body of research has suggested a more extended surgical approach creating large sinonasal cavities with gravity-dependent drainage pathways, followed by adjuvant medical therapies, as an ideal strategy to optimally control disease and prevent pulmonary exacerbations. In this manuscript, we provide an up-to-date review of current evidence in the surgical management of chronic rhinosinusitis in cystic fibrosis patients.